Pengaruh Price Discount dan Shopping Lifestyle Terhadap Impulse Buying Pada Konsumen Shopee di Kabupaten Garut - Nizar Alam Hamdani; Meli Kamila Muharwiyah; Rohimat Nurhasan (Entrepreneurship Faculty, Universitas Garut, 2022)
In this study to find out how X1 and X2 affect Y. The method this time is descriptive and verification methods. The number of samples is as many as 100 respondents using judgmental sampling technique is a sample with a limit of respondents who meet the requirements. By using SmartPLS 3.0. In this study, it is shown that the first hypothesis is that X1 has an effect on Y. The second hypothesis is that X2 has an effect on Y.